A study of humidity effect toward the quality of air from air conditioning system - Mohd Zamri, Mohd Kama (2012)
This thesis is about study of humidity effect towards quality of air using air conditioning unit at Mechanical Engineering Faculty (FKM) University Malaysia Pahang (UMP). Humidity is the quality of how much water or moisture content in the air. This project is to analyze the effect of dehumidification towards quality of air from air conditioning unit. The dehumidification method is using heater which is supplied before and after the evaporator. Variable speed of airflow is conducted to determine the effect of airspeed toward dehumidification. Analysis is done by giving different value of airspeed and different humidity. Experiment is conducted using air conditioning unit at thermodynamic laboratory which 24 experiments were done by giving different value of fan speed and humidity. Effect of pre-heater and re-heater also being monitored by varies the situation inside the air conditioning duct by switch on and off both of the heaters. After each experiment is being conducted, the quality of air at the exit is monitored and plotted on Psychrometric chart. Standard ASHRAE thermal comfort zone is used to determine the optimum temperature and humidity for thermal comfort. Various graphs is plotted and to determine the effect of humidification toward various parameters such as Coefficient of Performance (COP) of refrigerant, point temperatures, amount of heat being transferred and humidity. From the results, by increasing the velocity will help to make the environment become more comfortable. Secondly, increasing air velocity flow through evaporator increase its heat transfer and be calculated using energy balance equation. Besides that, from the experiment pre-heater and re-heater help to adjust the humidity and temperature at each point. Then, usage of humidifier causing the temperature and humidity to became further away from thermal comfort zone. Thus without using the humidifier, the quality of air from air conditioning unit FKM UMP can be improved.